An integrative approach to inter-organizational system implementation and evaluation: the case of government to business - Kassim, Erne Suzila; Hussin, Husnayati (IBIMA Publishing, 2010)
Over the years, government-to-business (G2B) as an inter-organizational system has emerged as an essential part of e-government systems. Its development and usage have not only been expected to contribute to efficient and effective operations, but G2B is also anticipated for better transparency, reduced costs and improved process. However, although a rich body of literature exists regarding G2B, there is a lack of empirical research finding in understanding the system from multiple stakeholders’ perspectives. Hence, using a qualitative case study research approach, we seek to understand the inter-organizational system motivations, issues and challenges for its implementation and success evaluation from the context of system sponsor, government agencies and business organizations. Using the Malaysian background, a specific G2B system is being investigated which is the public e-procurement system. Discussion of the case findings is offered and implications of the study are explained. Keywords: inter-organizational system, government-to-business, public e-procurement system.